Detection of sulfur mustard simulants using the microwave atmospheric pressure plasma optical emission spectroscopy method - Xu, Dexin; Li, Cong; Yang, Liu; Zhu, Wenchao; Huang, Bangdou; Zhang, Cheng; Shao, Tao (Frontiers in Chemistry, 2023)
Sulfur mustard (SM) is one kind of highly toxic chemical warfare agent and easy to spread, while existing detection methods cannot fulfill the requirement of rapid response, good portability, and cost competitiveness at the same time. In this work, the microwave atmospheric pressure plasma optical emission spectroscopy (MW-APP-OES) method, taking the advantage of non-thermal equilibrium, high reactivity, and high purity of MW plasma, is developed to detect three kinds of SM simulants, i.e., 2-chloroethyl ethyl sulfide, dipropyl disulfide, and ethanethiol. Characteristic OES from both atom lines (C I and Cl I) and radical bands (CS, CH, and C2) is identified, confirming MW-APP-OES can preserve more information about target agents without full atomization. Gas flow rate and MW power are optimized to achieve the best analytical results. Good linearity is obtained from the calibration curve for the CS band (linear coefficients R2 > 0.995) over a wide range of concentrations, and a limit of detection down to sub-ppm is achieved with response time on the order of second. With SM simulants as examples, the analytical results in this work indicate that MW-APP-OES is a promising method for real-time and in-site detection of chemical warfare agents.